Feline Interstitial Cystitis - Analysis of Clinical-epidemiological Findings and Inflammatory Biomarkers - da Silva, Renata Borges; da Silva, Lívia Queiroz; Ximenes, Poliana Araújo; Araújo, Vitória Maria Jorge; da Silva, Isaac Neto Goes; de Morais, Nina Bezerra; da Silva, Narah Kessia Castro; Ferreira, Tiago Cunha (Acta Scientiae Veterinariae, 2025)
Background: Feline Interstitial Cystitis (FIC) is a prevalent condition within Feline Lower Urinary Tract Diseases (FLUTD), frequently affecting male, mixed-breed cats aged 1-10 years. Despite its high incidence, data on FIC in Ceará, Brazil, remain limited. This study evaluates the prevalence of FIC among cats treated at the Veterinary Hospital of Ceará State University (UECE) and explores the utility of inflammatory biomarkers, including the serum albumin/creatinine ratio (SACR) and urine specific gravity/albumin ratio, as potential diagnostic and prognostic tools for disease monitoring. Materials, Methods & Results: This study evaluated 227 cats diagnosed with FIC among 3,900 treated at the Veterinary Hospital of Ceará State University, indicating a prevalence of 5.82%. Data were collected on sex, age, reproductive status, diet, clinical signs, urinalysis results, and laboratory parameters including urine specific gravity (USG), creatinine, albumin, and inflammatory biomarker ratios (SACR and USG/albumin). Of the 227 cats, 102 presented with the obstructive form (OC) and 125 with the non-obstructive form (NOC). All OC cats were male, 75% were intact, and 25% neutered, while 56% of NOC cats were female. The clinical signs observed in OC cats included hematuria (69.6%), dysuria (50%), periuria (19.6%), stranguria (18.6%), and polyuria (4.9%). Dry food predominated as the primary diet in 80% of OC and 83% of NOC cats. Urinalysis showed struvite crystals in 41% of OC and 28% of NOC cats, while 55.8% of OC and 69.6% of NOC cats had no crystals. Laboratory analysis revealed no significant differences between groups for USG, creatinine, and albumin levels. However, SACR values were lower in OC cats compared to NOC cats, and the USG/albumin ratio showed no statistical difference between groups. Discussion: This study highlights the prevalence of FIC at 5.82% in cats treated at the Veterinary Hospital of Ceará State University, providing important insights into its clinical and epidemiological characteristics. The findings confirm that male cats are disproportionately affected by the obstructive form (OC), with 100% of cases occurring in males, of which 75% were intact. Hematuria, dysuria, and periuria were the most frequent clinical signs in OC cases, aligning with previous studies. The predominance of dry food as the primary diet in both OC and NOC groups underscores its potential role in urinary health, although no direct causation was established. Urinalysis revealed a higher occurrence of struvite crystals in OC cases (41%) compared to NOC (28%), while more NOC cats had no crystals (69.6%). These findings suggest that other factors, beyond crystalluria, contribute to the inflammatory processes underlying FIC. The significant reduction in serum albumin/creatinine ratio (SACR) in OC cats emphasizes its potential as a biomarker for inflammation and impaired renal function. However, the lack of difference in USG/albumin ratio between groups suggests that additional studies are needed to validate its clinical utility. In conclusion, the study underscores the epidemiological and clinical relevance of FIC, emphasizing the potential of SACR as a diagnostic and monitoring tool. Further prospective studies are encouraged to deepen the understanding of the disease’s pathophysiology and explore the role of inflammatory biomarkers in its management. Keywords: lower urinary tract disease, urine specific gravity, epidemiology, albumin to creatinine ratio.